Deformation and Stability Analysis of a Core Rockfill Dam with Leakage. (29th August 2022) - Chen, Yuanzhong; Lin, Guobing; Lu, Yangyang
Abstract : The No. 4 clay core rockfill dam of the Gongming Reservoir experienced leakages when the reservoir water level was low. To analyze the leakage causes, a series of seepage tests were conducted on the dam materials in this paper. And a three-dimensional finite element stress-seepage coupled calculation model of the dam was established to study the deformation and stresses of the dam under the condition of normal storage water level and the sharp drop in the storage level. The test results show that the permeability coefficient of the clay core material is close to that of the dam shell material, resulting in the leakage of the dam under the condition of the low-water level. The simulation results show that the dam deforms a little under the condition of normal storage water level and the sharp drop in the storage level, and the stress distribution under the condition of the sharp drop in the storage level is basically consistent with that under the condition of normal storage water level. The safety factors of the dam under the two conditions meet the requirements of the specification, but the margin of the safety factor is small.